SYSTEM OF VISUAL IDENTIFICATION IN CREATION OF THE TOURISTIC BRAND AND ACTIVATION OF THE REGION - Łuczak, Mariola (Acta Scientiarum Polonorum. Oeconomia, 2010)
The region’s image consists of impressions, experiences and feelings it evokes in the surrounding. The region’s image is not something stable and permanent, it can be continuously improved, meaning developed and changed. The visual identity is a part of marketing communication, which no touristic place should ignore during forming or modifying a strategy. It is one of the most important parts of a general identity and gives us foundations for aware building of place image. And so it belongs to add at constructing visual identification any efforts, in order to they solidified the image at tourists of associating emerging, it depends on that area and they strengthened the superiority of the competitive touristic place in a communication dimension.